Potensi Peredaran Kosmetik Dalam Bentuk Mainan (Mainan Kosmetik) Tidak Memiliki Izin Edar - Sende, Iin Febrianti; Kembaren, Anita; Yunianto , Edi Priyo; Barus , David Julianto; Arrahman , Yovia Rizki (Badan Pengawas Obat dan Makanan, 2023)
Cosmetics in the form of children's toys/cosmetic toys such as eyeshadow, lipstick/lip gloss, blush on, nail polish, and others are popular among children. Cosmetic toys distributed offline in toy shops/online in the marketplace. Cosmetic toys have the potential to contain harmful ingredients such as mercury, formaldehyde, etc. These ingredients have the potential to cause health problems, especially in children who have immature skin protective functions and immune systems. Nowadays, there is still a dualism in the distribution license of cosmetic toys: as cosmetics that must have a notification number from Indonesian FDA or as toys which must have SNI standards and be produced by toys manufacturers. The research aims to determine trends in the circulation of cosmetic toys and the potential impact of license dualism to ensure the safety of cosmetic toys in circulation. The research was conducted by collecting data on cosmetic toys in 48 toy shops in Jakarta, Bogor, Depok, Tangerang, Bekasi, Denpasar, and Surabaya areas in period of April – June 2023. The results of the research showed that all cosmetic toys are decorative cosmetics, and most often as toys with SNI marking. Most of the cosmetic toys in circulation are import products from China. Besides that, in circulation it was also found there are cosmetic toys do not have a distribution permit (illegal) and/or also have a double category as toys and cosmetics. This could be a loophole for business actors who produce or sell illegal cosmetic toys that have the potential to contain dangerous ingredients and could cause losses for business actors who register their products in both categories. BPOM needs to coordinate with related sectors to review regulations on cosmetic toy products to determine the boundaries between toys and cosmetics.